2020
DOI: 10.3390/ijms21103558
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Chronic Liver Disease in Individuals from Pakistan

Abstract: Chronic liver disease, with viral or non-viral etiology, is endemic in many countries and is a growing burden in Asia. Among the Asian countries, Pakistan has the highest prevalence of chronic liver disease. Despite this, the genetic susceptibility to chronic liver disease in this country has not been investigated. We performed a comprehensive analysis of the most robustly associated common genetic variants influencing chronic liver disease in a cohort of individuals from Pakistan. A total of 587 subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Genotyping was performed using TaqMan probes 31 . The genotypes of PNPLA3 (rs738409), TM6SF2 (rs58542926), MBOAT7 (rs641738) and GCKR (rs1260326) were analysed using commercially available TaqMan probes and a 7500 Fast Real‐Time PCR System, both from Thermo Fisher, according to the manufacturer's instruction 30 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping was performed using TaqMan probes 31 . The genotypes of PNPLA3 (rs738409), TM6SF2 (rs58542926), MBOAT7 (rs641738) and GCKR (rs1260326) were analysed using commercially available TaqMan probes and a 7500 Fast Real‐Time PCR System, both from Thermo Fisher, according to the manufacturer's instruction 30 …”
Section: Methodsmentioning
confidence: 99%
“…Three 10‐μm sections of FFPE blocks were processed according to the manufacturer's protocol (User bulletin, Version: MAN0010642 Rev. D.0) and as previously described 30 . Briefly, the FFPE slides were deparaffinized and digested with protease.…”
Section: Methodsmentioning
confidence: 99%
“…Only a single study on the present subject is available from Pakistan that reported a significant prevalence of PNPLA3 risk variant, but not TM6SF2 polymorphism, in end stage hepatic ailment patients with mixed etiology (viral as well as non-viral origin) who received living donor liver transplantation, when compared to normal controls [18].…”
Section: Univariate Regression Analysismentioning
confidence: 87%
“…To this point, despite the fact that PNPLA3 and TM6SF2 polymorphisms represent most commonly investigated lipid metabolism based host genetic variants in NAFLD, their potential influence in CHC mediated CLP is less defined. Additionally, PNPLA3 and TM6SF2 variants based genetic predisposition to liver scarring data in CHC patients is mainly available for different Caucasian ethnic groups with scarce representation of other populations, together with Indo-Pak region and mixed populations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Asian countries, Seko Y et al described that the HSD17B13 genetic variant attenuated the risk of the PNPLA3 minor allele for NAFLD [ 40 ]. Regardless of FLD, the protective effects of this variant on ALD or any chronic liver diseases were confirmed among the Chinese or Pakistani population [ 41 , 42 ].…”
Section: Role Of Hsd17b13 Genetic Variants In Liver Diseasementioning
confidence: 99%